2010
DOI: 10.1111/j.1755-5922.2010.00148.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Aliskiren Monotherapy and Ramipril Monotherapy in Patients with Stage 2 Systolic Hypertension: Subgroup Analysis of a Double‐blind, Active Comparator Trial

Abstract: Aliskiren is the first direct renin inhibitor approved for the treatment of hypertension. Blood pressure (BP) control in stage 2 hypertension with aliskiren monotherapy has not been reported. This was a post hoc analysis of the subgroup of patients with stage 2 systolic hypertension (baseline mean sitting systolic BP [msSBP] ≥160 mmHg) who completed the 12-week monotherapy phase of a 6-month, double-blind, randomized study. A total of 175 patients were randomized to aliskiren 150 mg (n = 88) or ramipril 5 mg (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…17 At 24 weeks, SBP goals (<135 mm Hg) is achieved by 89.58% while for DBP is 87.50% (< 85 mmHg) in our study (Table 6). …”
Section: Group Bmentioning
confidence: 71%
See 1 more Smart Citation
“…17 At 24 weeks, SBP goals (<135 mm Hg) is achieved by 89.58% while for DBP is 87.50% (< 85 mmHg) in our study (Table 6). …”
Section: Group Bmentioning
confidence: 71%
“…16,17 Comparison between Group A and Group B On comparing Amlodipine therapy (Group A) versus Ramipril therapy (Group B), it was found that both the therapies are equally effective in improving the SBP, DBP and MAP at 12 and 24 weeks (Table 3 and Table 4). Whereas, both the therapies had not shown statistically significant difference on the blood urea, s. sodium, s. potassium, s. chloride, s. bilirubin, SGOT and SGPT levels at 12 weeks and 24 weeks, respectively.…”
Section: Group Bmentioning
confidence: 99%
“…HDL level rises at 6 weeks was less as revealed by Jayram et al while it was more than as observed by Shepherd et al [17] and Yamazaki et al [11] at 12 weeks. SBP and DBP fall by 13.72% and 19.52% that were more as revealed by MacMohan et al (5.26% and 5.06% respectively, with ramipril 5-10 mg/day) [18], Anderson K et al (5.26% and 5.06% with ramipril 5-10 mg /day) [19] and Lonn et al (4.52% and 2.618% with ramipril 10 mg/day at 4 weeks) [14] but less as observed by Soni U et al (25.40% and 16.89% with ramipril 10 mg/day at 12 weeks) [20].…”
Section: Group IImentioning
confidence: 75%
“…Use of an aliskirenbased regimen has shown an advantage over an ARB-based regimen in its ability to reduce BP in patients with metabolic syndrome (33). Aliskiren has also demonstrated improved efficacy over ACE inhibitors, in patients with moderate-to-severe hypertension (34). Differences in drug efficacy and metabolism based on ethnic variations are widely acknowledged.…”
Section: Discussionmentioning
confidence: 99%